Association between clinical manifestations of sickle cell anaemia in children and the occurrence of dental caries: A cross-sectional study - Carvalho, Anderson Santos; Duarte, Danilo Antônio da Silva; Antunes, José Leopoldo Ferreira; Cangussu, Maria Cristina Teixeira; Cangussu, Maria Cristina Teixeira (Brazilian Dental Science, 2020)
Objective: The aim of this study was to determine the association between clinical manifestations of sickle cell anemia (including hospitalization and pain crisis) and dental caries in children in Bahia. Material and Methods: The study design was crosssectional, and the population included children aged from 6 to 96 months from August 2007 to July 2008 (N = 686). Interviews were performed to identify the sociodemographic profiles of the participants, and oral examinations were conducted by three examiners who were previously trained and calibrated to identify the presence of dental caries according to World Health Organization (WHO) criteria. Logistic regression analysis was performed for confirmatory analysis and estimation of confidence intervals (CIs). Results: The results showed that pain crises and hospitalizations were positively associated with caries (crude odds ratio (OR) = 2.11 and adjusted OR = 1.24; crude OR = 2.50 and adjusted OR = 1.46, respectively), but these associations were not statistically significant. Conclusion: The severity of the sickle cell condition alone was not sufficient to aggravate the prevalence of caries; thus, there are no major differences in caries prevalence between children with and without sickle cell disease.KEYWORDSSickle cell anemia; Dental caries; Epidemiology; Paediatrics.